Prediction of pre‐eclampsia: review of reviews - Townsend, R.; Khalil, A.; Premakumar, Y.; Allotey, J.; Snell, K. I. E.; Chan, C.; Chappell, L. C.; Hooper, R.; Green, M.; Mol, B. W.; Thilaganathan, B.; Thangaratinam, S.; et al. (Ultrasound in obstetrics & gynecology, 2019)
ABSTRACT Objective Primary studies and systematic reviews provide estimates of varying accuracy for different factors in the prediction of pre‐eclampsia. The aim of this study was to review published systematic reviews to collate evidence on the ability of available tests to predict pre‐eclampsia, to identify high‐value avenues for future research and to minimize future research waste in this field. Methods MEDLINE, EMBASE and The Cochrane Library including DARE (Database of s of Reviews of Effects) databases, from database inception to March 2017, and bibliographies of relevant articles were searched, without language restrictions, for systematic reviews and meta‐analyses on the prediction of pre‐eclampsia. The quality of the included reviews was assessed using the AMSTAR tool and a modified version of the QUIPS tool. We evaluated the comprehensiveness of search, sample size, tests and outcomes evaluated, data synthesis methods, predictive ability estimates, risk of bias related to the population studied, measurement of predictors and outcomes, study attrition and adjustment for confounding. Results From 2444 citations identified, 126 reviews were included, reporting on over 90 predictors and 52 prediction models for pre‐eclampsia. Around a third (n = 37 (29.4%)) of all reviews investigated solely biochemical markers for predicting pre‐eclampsia, 31 (24.6%) investigated genetic associations with pre‐eclampsia, 46 (36.5%) reported on clinical characteristics, four (3.2%) evaluated only ultrasound markers and six (4.8%) studied a combination of tests; two (1.6%) additional reviews evaluated primary studies investigating any screening test for pre‐eclampsia. Reviews included between two and 265 primary studies, including up to 25 356 688 women in the largest review. Only approximately half (n = 67 (53.2%)) of the reviews assessed the quality of the included studies. There was a high risk of bias in many of the included reviews, particularly in relation to population representativeness and study attrition. Over 80% (n = 106 (84.1%)) summarized the findings using meta‐analysis. Thirty‐two (25.4%) studies lacked a formal statement on funding. The predictors with the best test performance were body mass index (BMI) > 35 kg/m2, with a specificity of 92% (95% CI, 89–95%) and a sensitivity of 21% (95% CI, 12–31%); BMI > 25 kg/m2, with a specificity of 73% (95% CI, 64–83%) and a sensitivity of 47% (95% CI, 33–61%); first‐trimester uterine artery pulsatility index or resistance index > 90th centile (specificity 93% (95% CI, 90–96%) and sensitivity 26% (95% CI, 23–31%)); placental growth factor (specificity 89% (95% CI, 89–89%) and sensitivity 65% (95% CI, 63–67%)); and placental protein 13 (specificity 88% (95% CI, 87–89%) and sensitivity 37% (95% CI, 33–41%)). No single marker had a test performance suitable for routine clinical use. Models combining markers showed promise, but none had undergone external validation. Conclusions This review of reviews calls into question the need for further aggregate meta‐analysis in this area given the large number of published reviews subject to the common limitations of primary predictive studies. Prospective, well‐designed studies of predictive markers, preferably randomized intervention studies, and combined through individual‐patient data meta‐analysis are needed to develop and validate new prediction models to facilitate the prediction of pre‐eclampsia and minimize further research waste in this field. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd. RESUMEN Predicción de la preeclampsia: revisión de revisiones Objetivo Los estudios primarios y las revisiones sistemáticas proporcionan estimaciones de precisión variable para diferentes factores en la predicción de la preeclampsia. El objetivo de este estudio fue revisar las revisiones sistemáticas publicadas para recopilar evidencia sobre la capacidad de las pruebas disponibles para predecir la preeclampsia, identificar avenidas de investigación futura valiosas y minimizar el desperdicio futuro de investigación en este campo. Métodos Se realizaron búsquedas de artículos relevantes en bibliografías sobre el tema y en las bases de datos MEDLINE, EMBASE y The Cochrane Library, incluida DARE (Database of s of Reviews of Effects), desde el inicio de cada base de datos hasta marzo de 2017, sin restricciones de idioma, para obtener revisiones sistemáticas y metaanálisis sobre la predicción de la preeclampsia. La calidad de las revisiones incluidas se evaluó utilizando la herramienta AMSTAR y una versión modificada de la herramienta QUIPS. Se evaluó la amplitud de la búsqueda, el tamaño de la muestra, las pruebas y los resultados evaluados, los métodos de síntesis de datos, las estimaciones de la capacidad de predicción, el riesgo de sesgo relacionado con la población estudiada, la medición de los predictores y los resultados, la deserción del estudio y el ajuste por confusión. Resultados De las 2444 citas identificadas, se incluyeron 126 revisiones, que informaron sobre más de 90 predictores y 52 modelos de predicción para la preeclampsia. Alrededor de un tercio (n=37 (29,4%)) de todas las revisiones investigaron únicamente marcadores bioquímicos para predecir la preeclampsia, 31 (24,6%) investigaron asociaciones genéticas con la preeclampsia, 46 (36,5%) informaron sobre las características clínicas, cuatro (3,2%) evaluaron sólo marcadores ecográficos y seis (4,8%) estudiaron una combinación de pruebas; dos (1,6%) revisiones adicionales evaluaron los estudios primarios que investigaron cualquier prueba de diagnóstico de la preeclampsia. Las revisiones incluyeron entre dos y 265 estudios primarios, que incluyeron hasta 25 356 688 mujeres en la revisión más grande. Sólo aproximadamente la mitad (n=67 (53,2%)) de las revisiones evaluaron la calidad de los estudios incluidos. En muchas de las revisiones incluidas hubo un alto riesgo de sesgo, particularmente en relación con la representatividad de la población y la deserción de los estudios. Más del 80% (n=106 (84,1%)) resumió los hallazgos utilizando el metaanálisis. Treinta y dos (25,4%) estudios carecían de una declaración formal sobre la financiación. Los predictores con el mejor rendimiento de la prueba fueron el índice de masa corporal (IMC) >35 kg.m–2, con una especificidad del 92% (IC 95%, 89–95%) y una sensibilidad del 21% (IC 95%, 12–31%); IMC >25 kg.m–2, con una especificidad del 73% (IC 95%: 64–83%) y una sensibilidad del 47% (IC 95%: 33–61%); índice de pulsatilidad de la arteria uterina en el primer trimestre o índice de resistencia >90° percentil (especificidad del 93% (IC 95%: 90–96%) y sensibilidad del 26% (IC 95%: 23–31%)); factor de crecimiento placentario (especificidad 89% (IC 95%, 89–89%) y sensibilidad 65% (IC 95%, 63–67%)); y proteína placentaria 13 (especificidad 88% (IC 95%, 87–89%) y sensibilidad 37% (IC 95%, 33–41%)). Ningún marcador por sí solo tuvo un rendimiento de la prueba adecuado para el uso clínico rutinario. Los modelos que combinan marcadores son prometedores, pero ninguno fue sometido a una validación externa. Conclusiones Esta revisión de revisiones ha puesto en duda la necesidad de un metaanálisis agregado adicional en esta área, dado el gran número de revisiones publicadas sujetas a las limitaciones comunes de los estudios predictivos primarios. Se necesitan estudios prospectivos bien diseñados de marcadores predictivos, preferiblemente en estudios de intervención aleatorios, y combinados mediante el metaanálisis de datos de pacientes individuales, para desarrollar y validar nuevos modelos predictivos que faciliten la predicción de la preeclampsia y minimicen el desperdicio de investigación adicional en este campo. 摘要 先兆子痫的预测:评论回顾 目的 初步研究和系统评论根据预测先兆子痫的不同因素提供各种准确的估计值。本研究的目的是回顾已发表的系统评论，核对现有检测能力的证据以便预测先兆子痫，确定未来研究的高价值途径，并尽量减少该领域未来研究的浪费。 方法 检索联机医学文献分析和检索系统(MEDLINE)、荷兰医学文摘数据库(EMBASE)和Cochrane图书馆包括DARE(效果评论摘要数据库)，从建立数据库到2017年3月，并检索了相关文章的参考文献，不受语言限制，对先兆子痫的预测进行系统回顾和meta分析。使用多系统评价膀胱问卷(AMSTAR)工具和QUIPS处理系统工具的修改版本评估纳入评论的质量。我们评估了搜索的全面性、样本大小、测试和评价结果、数据综合方法、预测能力估计、与研究人群相关的偏差风险、预测因素和结果的测量值、研究淘汰率和混杂设计的调整。 结果 共确定2444篇引文，其中包括126篇评论，报道了90多个预测因素和52种先兆子痫的预测模型。约三分之一(n=37(29.4%)的评论只研究了预测先兆子痫的生化标记，31篇(24.6%)研究了与先兆子痫的遗传关联，46篇(36.5%)报告了临床特征，4篇(3.2%)仅评价了超声标志物，6篇(4.8%)研究了联合检测；另外两篇(1.6%)评论评估了对先兆子痫筛查试验的初步研究。评论包括两项和265项初步研究，其中最大型评论纳入了多达25,356,688名女性。只有大约一半(n=67(53.2%))的评论评估了纳入研究的质量。许多纳入的评论有很高的偏差风险，特别是在人群代表性和研究淘汰率方面。80%(n=106(84.1%)以上的评论采用Meta分析方法总结研究结果。32项研究(25.4%)缺乏关于资金的正式说明。最佳检测指标为体重指数(MBI)>35 kg.m‐2，特异性92%(95% CI，89‐95%)，敏感性21%(95% CI，12‐31%)；BMI>25 kg.m‐2，特异性73%(95% CI，64‐83%)，敏感性47%(95% CI，33‐61%)；妊娠早期子宫动脉搏动指数或阻力指数>90%(特异性93%(95% CI，90%‐96%)和敏感性26%(95% CI, 23%–31%))；胎盘生长因子(特异性89%(95% CI，89%‐89%)，敏感性65%(95% CI，63%‐67%)；胎盘蛋白13(特异度88%(95% CI，87%‐89%)，敏感性37%(95% CI, 33%–41%))。 没有一种单一标记物具有适合常规临床使用的测试性能。模型结合标记物显示有希望，但没有一种模型经过外部验证。 结论 鉴于大量已发表的评论受制于初级预测研究的共同局限性，本评论回顾引发了对这一领域进行进一步汇总meta分析的必要性的质疑。为了开发和验证新的预测模型，促进对先兆子痫的预测，并最大限度地减少该领域的进一步研究浪费，需要对预测标志物进行前瞻性、精心设计的研究，最好是随机干预研究，并与个体患者数据的meta分析相结合。 This article's has been translated into Spanish and Chinese. Follow the links from the to view the translations.